Reframing development in Ireland: making the case for an urban lab approach. Issue 10 (3rd October 2021) - Collins, Patrick; Strohmayer, Ulf; Rainey, Mark Justin
ABSTRACT: In this paper, we map the evolution of approaches to development in Ireland since the formation of the state. With reference to the current national and international context, we make the case for the adoption of a transformational approach to development in one of Europe's most centralized countries. We highlight the growing literature on socio-ecological approaches to growth and consider the potential for the development of an urban lab to enable a radical shift in approaches to development in Ireland. The paper shines a light on certain initiatives already underway in Galway, Ireland and posits their culmination in the delivery of an urban lab for the city. In particular, we cite the opportunities afforded by urban labs to better define growth (a more socio-ecological definition of innovation) and facilitate the co-authoring of development through place-based experimentalism at the local level.